ACADEMIC INFORMATION SYSTEM AT MUHAMMADIYAH HIGH SCHOOL KUDUS USING MOVING AVERAGE TO DETERMINE MASTERY STANDARD - Amara, Radinda; Nugraha, Fajar; Setiawan, R Rhoedy (Institut Teknologi Nasional Malang, 2025)
The utilization of information technology has been widely applied in various fields, including the education sector. However, at Muhammadiyah High School Kudus, administrative tasks such as student data management, class scheduling, attendance tracking, and report card generation still rely on Microsoft Word and Microsoft Excel, leading to inefficiencies and a high risk of human error. This study aims to develop a web-based Academic Information System to streamline administrative processes and improve data accuracy by integrating the Moving Average method to determine the Minimum Mastery Standard (SKBM) based on historical student performance data. The system is developed using the Waterfall method, with PHP as the programming language and MySQL as the database for efficient data management. Blackbox testing is conducted to evaluate system functionality, ensuring its reliability and accuracy. The results indicate that the proposed system significantly enhances administrative efficiency, reduces errors in academic data processing, and provides a more accurate SKBM determination. This research contributes to educational institutions by offering a systematic approach to academic performance evaluation, ultimately supporting better decision-making in student assessments and learning outcomes.